2019
DOI: 10.1111/jors.12467
|View full text |Cite
|
Sign up to set email alerts
|

Transport corridors and their wider economic benefits: A quantitative review of the literature

Abstract: Transport corridors can generate both wider economic benefits (WEBs) and costs through their effects on diverse development outcomes. To advance understanding of how corridors could generate WEBs, this paper undertakes a quantitative review and meta‐analysis of the literature that estimates the impacts of large transport infrastructure projects. The analysis finds that characteristics of individual studies and the design of the transport infrastructure influence estimated benefits. It also shows that, on avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…It is worth to note that the literature found evidence of these negative effects of corridor interventions. Roberts et al (2019, p. 2), in a meta‐analysis of this literature, found that “on average, while corridor interventions tend to benefit economic welfare and equity, they often detrimentally impact the environment. In order to mitigate trade‐offs, policymakers can consider using complementary interventions.” Freitas (2016) also suggested complementary interventions for the BRT in Belo Horizonte.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to note that the literature found evidence of these negative effects of corridor interventions. Roberts et al (2019, p. 2), in a meta‐analysis of this literature, found that “on average, while corridor interventions tend to benefit economic welfare and equity, they often detrimentally impact the environment. In order to mitigate trade‐offs, policymakers can consider using complementary interventions.” Freitas (2016) also suggested complementary interventions for the BRT in Belo Horizonte.…”
Section: Discussionmentioning
confidence: 99%
“…The property typology that we analyse—residential, commercial, vacant urban land, rural, mixed‐use—may also cause significant variations. Although there is evidence of it in the recent empirical literature (Debrezion, Pels, & Rietveld, 2007; Leishman & Watkins, 2017; Roberts, Melecky, Bougna, & Xu, 2019), studies usually have the opportunity to test just one intervention in one city.…”
Section: Introductionmentioning
confidence: 99%
“…In the general case, the models and systems of zones reflect the specific historical patterns of "inherited development" ("Path Dependence") for the macroregion [7,8]. Further, against their background, new trends are considered: urbanization [9] (associated with agglomeration processes and the formation of agglomerations), transformation of communications (associated with migration, change in logistics and development of transport corridors [10,11]).…”
Section: Methodsmentioning
confidence: 99%
“…While a few pioneering studies have provided reviews of the impact assessment of transport systems on related topics, such as multimodal transportation (Roberts, Melecky, Bougna, & Xu, 2020), land and housing impact (Bešinović, 2020;Wu, Zheng, Wang, & Du, 2020), and competition of HSR with aviation (Zhang, Wan, & Yang, 2019), there is still a lack of a comprehensive and systematic review of socioeconomic impact assessment of the HSR system.…”
Section: Introductionmentioning
confidence: 99%